Education on the Potential of Fish Nutrients to Coastal Housewives in Leppe Village - Muchtar, Febriana; Lisnawaty, Lisnawaty; Suhadi, Suhadi; Zaiunuddin, Asnia; Salsabila, Syefira (Abdi Masyarakat, 2023)
Fish is one of the potential food sources of animal protein produced in coastal areas. The use of fish as a source of animal food by coastal communities has been carried out for generations because it is the easiest food source to be processed into daily side dishes for coastal households. Fish contains quality nutrients, both macronutrients and micronutrients. The condition of coastal housewives who lack information about the nutritional content of fish and its benefits is the background for implementing this community service activity. The aim of the activity is to increase the knowledge of coastal communities, especially housewives, so that they can utilize the nutritional potential of fish through the processing and consumption of fish to fulfill the family's nutritional intake.Coastal housewives were very enthusiastic during the activity which was marked by answering several questions in the question and answer process. The results of the evaluation showed that education can provide an understanding of fish nutrition and its benefits, where the percentage of correct answers reached 94.54%. Coastal housewives are expected to be able to utilize the nutritional potential of fish which is a source of quality animal food that is easily obtained in coastal areas.